The Importance of Educational Psychology in Islamic Education Management - Saidin; Iskandar; Yamin, Martinis (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2023)
Psychology is a science that studies the soul, therefore psychology is closely related to education and has an important role in educational management. This research aims to analyze and describe the importance of educational psychology in Islamic education management. The approach in this research uses a literature study approach. In this study there was no research location, because all data was taken from journals, books and scientific proceedings. The object of this research is the importance of educational psychology in the management of Islamic education, as for data collection techniques using documentation, and data analysis techniques through data reduction, data presentation and drawing conclusions. The results of this research can be described that psychology is a science that studies human behavior, psychology has its roots in the philosophy of science starting from the time of Aristotle as a science of the soul, while educational psychology is a scientific discipline that studies human behavior in the world of education. Next, Islamic education management in practice is implementing the principles and functions of management in Islamic education institutions. The importance of educational psychology is to provide recipes on how to manage Islamic education successfully.